Principals' emotions in school improvement: the role of people, practices, policies, and patterns. (27th May 2022) - Park, Vicki; Datnow, Amanda
ABSTRACT: The work of principals has become increasingly challenging and complex, as they are expected to lead school improvement, manage -a host of competing demands, and attend to the needs of diverse stakeholders. However, the emotions related to principals' work, particularly in relation to educational reform, has been understudied in recent years. This paper investigates the emotional dimensions of principals' work with respect to school improvement and change, and how the people, practices, policies, and patterns in their school contexts intersect with their emotions and actions. Analyzing 42 interviews with 19 U.S. principals engaged in reform, we explain how managing change and teacher staffing and collaboration were particularly emotional processes for principals. Principals acted as mediators and managers of the emotional climate of their schools while also processing their own emotions. Implications for research and practice are discussed.